Squalomix: shark and ray genome analysis consortium and its data sharing platform [version 1; peer review: 2 approved] - Nishimura, Osamu; Rozewicki, John; Yamaguchi, Kazuaki; Tatsumi, Kaori; Ohishi, Yuta; Ohta, Tazro; Yagura, Masaru; Niwa, Taiki; Tanegashima, Chiharu; Teramura, Akinori; Hirase, Shotaro; Kawaguchi, Akane; et al. (F1000 research, 2022)
The taxon Elasmobranchii (sharks and rays) contains one of the long-established evolutionary lineages of vertebrates with a tantalizing collection of species occupying critical aquatic habitats. To overcome the current limitation in molecular resources, we launched the Squalomix Consortium in 2020 to promote a genome-wide array of molecular approaches, specifically targeting shark and ray species. Among the various bottlenecks in working with elasmobranchs are their elusiveness and low fecundity as well as the large and highly repetitive genomes. Their peculiar body fluid composition has also hindered the establishment of methods to perform routine cell culturing required for their karyotyping. In the Squalomix consortium, these obstacles are expected to be solved through a combination of in-house cytological techniques including karyotyping of cultured cells, chromatin preparation for Hi-C data acquisition, and high fidelity long-read sequencing. The resources and products obtained in this consortium, including genome and transcriptome sequences, a genome browser powered by JBrowse2 to visualize sequence alignments, and comprehensive matrices of gene expression profiles for selected species are accessible through https://github.com/Squalomix/info.